Komunikasi Pemerintahan Daerah Dalam Pembangunan Daerah Wisata di Kabupaten Magelang - Anggraeni, Suwastika; Eko Atmojo, Muhammad (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Communication has two different meanings, namely communication in a broad and narrow sense. Communication in a broad sense is the activity of exchanging messages that occurs reciprocally in the development process, especially communication between society and government. Communication in the narrow sense is an effort to convey messages in development to the communities involved. Apart from that, the government makes various efforts to communicate with the public. One of them is by conveying policies that have been set by the government and implementing them to the community. Various strategies are being sought by the government for the community in implementing government policies in implementing regional development in Magelang Regency. In implementing regional development programs there are several inhibiting factors. Apart from that, regional governments have the aim of implementing regional development to improve the economy in the area. This is an effort by the regional government to improve the welfare of the community. Apart from that, the tourism industry is currently one of the largest foreign exchange contributors for Indonesia, apart from the oil and gas industry, Indonesia is an agricultural country with abundant natural resources that can be utilized for tourism.